Clinical and aetiological spectrum of spontaneous pneumothorax in adults in Sub-Himalayan: a prospective study at tertiary care institute - Sharma, Ajay; Sharma, Ashok; Jaret, Pramod; Sarkar, Malay; Sharma, Sanjeev (International Journal of Scientific Reports, 2018)
Background: The spontaneous pneumothorax has been classified as major cause of morbidity and mortality among respiratory diseases. The objectives of the study were to determine the incidence and aetiology of spontaneous pneumothorax and to assess the clinical profile of affected patients admitted in our institute. Methods: A hospital based prospective study was conducted in year 2011-12 in the Department of Medicine, IGMC Shimla (H.P.) India. During study period the total admissions were 7335 out of which 30 patients were diagnosed as spontaneous pneumothorax and treated as cases under study. The data was collected on proforma includes demographic profile, probable cause, clinical and outcome indicators of Spontaneous Pneumothorax, master chart framed and analysed into frequency percentage. Results: Incidence of spontaneous pneumothorax was found to be 408.99/yr/100000 admissions in the department of medicine. Incidence of primary spontaneous pneumothorax was 81.79/yr/100000 admissions. Incidence of secondary spontaneous pneumothorax was 327.19/yr/100000 admissions. Majority of the patients of primary spontaneous pneumothorax were of the 20-29yrs age group. Higher proportions of cases were from male gender (93.33%). Secondary pneumothorax patients were mostly of 50 to 59 years age group. The predominant aetiology for secondary spontaneous pneumothorax was COPD (36.66%) followed by Pulmonary tuberculosis (33.33%). Conclusions: Spontaneous pneumothorax was more common in men. The predominant aetiology for secondary spontaneous pneumothorax was COPD (36.66%) followed by pulmonary tuberculosis (33.33%).